ChatGPT and Rhinoplasty Recovery: An Exploration of AI's Role in Postoperative Guidance - Capelleras, Marta; Soto-Galindo, Germán A.; Cruellas, Marc; Apaydin, Fazil (Facial Plastic Surgery, 2024)
The potential applications of artificial intelligence (AI) in health care have garnered significant interest in recent years. This study presents the first published exploration of ChatGPT, an AI language model, as a tool for providing postoperative guidance during rhinoplasty recovery. The primary objective was to shed light on the role of ChatGPT in augmenting patient care during the critical postoperative phase. Using the Rhinobase database, standardized questions were formulated to evaluate AI-generated responses addressing pain management, swelling, bruising, and potential asymmetries. Results demonstrated that ChatGPT has the potential to enhance patient education and alleviate emotional distress by providing general information and reassurance during the recovery process. However, the study emphasized that AI should not replace personalized advice from qualified health care professionals. This pioneering investigation offers valuable insights into the integration of AI and human expertise, paving the way for optimized postrhinoplasty recovery care.
Keywords: ChatGPT; rhinoplasty recovery; artificial intelligence